2020
DOI: 10.1016/j.ijrobp.2019.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Plan Selection in Proton Therapy of Locally Advanced Prostate Cancer with Simultaneous Treatment of Multiple Targets

Abstract: This study presented a method of plan selection in intensity modulated proton therapy to address the challenge of delivering treatment to the prostate and the pelvic lymph nodes with different motion patterns. The plan library used different positions of the prostate created from a population model of day-to-day target motion. Plan selection from this library reduced the dose to the rectum and bladder without compromising target coverage compared with nonadaptive delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Most studies addressing anatomic change during proton therapy have used CT-based offline adaptive approaches and have focused on adult cancers. [15][16][17][18] However, MRI-based adaptive therapy would be more appropriate for children because MRI enables better visualization of brain tumors and sarcomas, both of which are common in this patient population. In addition, MRI is not associated with additional radiation exposure, which is an important consideration in children.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies addressing anatomic change during proton therapy have used CT-based offline adaptive approaches and have focused on adult cancers. [15][16][17][18] However, MRI-based adaptive therapy would be more appropriate for children because MRI enables better visualization of brain tumors and sarcomas, both of which are common in this patient population. In addition, MRI is not associated with additional radiation exposure, which is an important consideration in children.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, known clinical effects of acute radiation exposure, such as mucositis and diarrhea, were shown to be affected by the gut microbiota in correlation with conditions of treatment and disease [132][133][134]; but little is known about the subsequently penetrating effects on functional metagenomics initiated by enteric microbial products and systemic metabolomics for the treatment of, for example, prostate cancer [135][136][137], which has been treated with conventional intensity-modulated radiation therapy [137] and intensitymodulated proton therapy [138]. Analyses between the gut microbiota and bone microstructure revealed that Bacteroides massiliensis and Muribaculum sp.…”
Section: Discussionmentioning
confidence: 99%